Microbial Cell-Free DNA Identifies Etiology of Bloodstream Infections, Persists Longer Than Conventional Blood Cultures, and Its Duration of Detection Is Associated With Metastatic Infection in Patients With Staphylococcus aureus and Gram-Negative Bacteremia. (30th August 2021) - Eichenberger, Emily M; de Vries, Christiaan R; Ruffin, Felicia; Sharma-Kuinkel, Batu; Park, Lawrence; Hong, David; Scott, Erick R; Blair, Lily; Degner, Nicholas; Hollemon, Desiree H; Blauwkamp, Timothy A; Ho, Carine; et al.
Abstract: Background: Microbial cell-free DNA (mcfDNA) sequencing of plasma can identify the presence of a pathogen in a host. In this study, we evaluated the duration of pathogen detection by mcfDNA sequencing vs conventional blood culture in patients with bacteremia. Methods: Blood samples from patients with culture-confirmed bloodstream infection were collected within 24 hours of the index positive blood culture and 48 to 72 hours thereafter. mcfDNA was extracted from plasma, and next-generation sequencing was applied. Reads were aligned against a curated pathogen database. Statistical significance was defined with Bonferroni adjustment for multiple comparisons ( P  < .0033). Results: A total of 175 patients with Staphylococcus aureus bacteremia (n = 66), gram-negative bacteremia (n = 74), or noninfected controls (n = 35) were enrolled. The overall sensitivity of mcfDNA sequencing compared with index blood culture was 89.3% (125 of 140), and the specificity was 74.3%. Among patients with bacteremia, pathogen-specific mcfDNA remained detectable for significantly longer than conventional blood cultures (median 15 days vs 2 days; P  < .0001). Each additional day of mcfDNA detection significantly increased the odds of metastatic infection (odds ratio, 2.89; 95% confidence interval, 1.53–5.46; P  = .0011). Conclusions: Pathogen mcfDNA identified the bacterial etiology of bloodstream infection for a significantly longer interval than conventional cultures, and its duration of detection was associated with increased risk for metastatic infection. mcfDNA could play a role in the diagnosis of partially treated endovascular infections. Abstract : Among patients with bacteremia, microbial cell-free DNA was detectable for significantly longer than conventional blood cultures and duration of detection was associated with metastatic infections.